Turnaround Strategies for Mature Industrial-Product Business Units. - Hambrick, D. C.; Schecter, S. M. (Academy of Management Journal, 1983)
A study of short-term turnaround attempts by mature industrial-product business units found that efficiency-oriented moves, but not entrepreneurial initiatives, were associated with successful turn...